Protein bound fucos, protein bound hexose and total calcium in sera of patient with thyroid dysfunction and control - Aitai, W.F.; AL-arrag, N.F; Rajab, T. M. A.; Hassan, H. G. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Protein bound fucose (PBF), protein  bound hexose (PBHex), and total calcium {T.Ca) were 'determined in sera of (40) hy-p.ertnyroidism , (40)  hypothyroidism patients and (40) controL The resultsr vealed  a significant decrease in the kwel of PBF,  PBHex and T.Ca in sera of patients with .hyperthyroidism  compared  to control; Inc se Qf PBF. there nQ difference in its level betwe.en patients with hypothyroidism and  control  group.  While there  is a significant increment in  PBHex leveli:n both hyper and hypothyroidism With respect to that of control Result  indicates, that total calcium levels were i.n  the nomml range for all p tients groups. Patient  compared   to control  no difference in  the level  of  (PBF) b tween   hypoth.yroid1sm  and  controL  A  significantincrea;;.e in the level of PBHex in sera of hyper and  hypothy:roidJsmcompared to controlwas found.